2019
DOI: 10.1186/s40068-019-0141-5
|View full text |Cite
|
Sign up to set email alerts
|

Land use−land cover changes and Mopani worm harvest in Mangwe District in Plumtree, Zimbabwe

Abstract: Background: Mopani worms have been considered a critical food security resource as people living in Mopani woodlands depend on the worms both as a food source and as an income generating resource. These become a readily available substitute if agriculture fails and droughts loom. However the yields from these worms have been dwindling over the years and this has been associated with land use−land cover changes as the worms depend on vegetation. This research sought to investigate the relationship between land … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…Climate change is a global problem that reduces precipitation and increases the extended drought in Southern Africa [ 71 , 72 ]. These changes have resulted in the decline of insect availability in the wild [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate change is a global problem that reduces precipitation and increases the extended drought in Southern Africa [ 71 , 72 ]. These changes have resulted in the decline of insect availability in the wild [ 71 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes have resulted in the decline of insect availability in the wild [ 71 , 73 ]. Other factors that might affect the availability of edible insects are different land uses such as clearing of land, development, agriculture, and deforestation [ 61 , 70 , 72 ]. Ndlovu [ 72 ] reported that 40% of the respondents in Zimbabwe cited that the cutting down of mopane trees for fuel use resulted in the decline in mopane worm yields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies on mopane worm governance in communal areas in Namibia have demonstrated that institutional coordination and stricter controls on access and monitoring are critical for mopane worm population sustainability (Thomas 2013, Ndeinoma andWiersum 2016). In Zimbabwe, diminished coordination, especially in communal areas, has led to widespread deforestation and habitat destruction in mopane woodlands (Ndlovu et al 2019). Under such scenarios, coordination may be beneficial when led by the state, especially in communal areas in which traditional and customary rules have been eroded and remain weak.…”
Section: Resource Degradation and Perceptions Of Environmental Changementioning
confidence: 91%
“…This is exacerbated by continuous demand driven harvesting to the detriment of wild populations. Changing land use patterns have also been shown to negatively affect wild insect population abundances and harvests due to conversion of land into agriculture, deforestation and decline in vegetation cover (20). Climate change driven environmental shifts also demand that we safeguard traditional harvesting and consumption practices of edible insects in several parts of Africa in order to ensure continued availability of these resources for future generations.…”
Section: Introductionmentioning
confidence: 99%